(ERRATUM) Vulnerability Assessment at Mt. Bromo Indonesia by Using Time-Series Land Surface Deformation and GIS - Arliandy P. Arbad; W. Takeuchi; Y. Aoki; Ahmad Ardy (POLITEKNIK NEGERI JAKARTA, 2019)
This paper